PATTERNS OF PRESENTATION OF CHRONIC ISCHEMIC HEART DISEASE WITH AND WITHOUT PREVIOUS MYOCARDIAL INFARCTION - Ahmad, Rehan; Rabbani, Aftab; Awan, Zahid Aslam (Journal of Ayub Medical College Abbottabad, 2009)
Background: The prevalence of Ischemic Heart Disease (IHD) is on the rise, from increasing lifespan of population and availability of better medical facilities. We studied chronic IHD cases with and without previous myocardial infarction, in Hazara, NWFP, Pakistan to evaluate left ventricular (LV) dysfunction, wall motion abnormalities and complications of IHD. Methods: All patients presenting with history of chest pain in Medical '˜C' Unit, Ayub Teaching Hospital, Abbottabad from June 2004 to May 2005 were included in the study. Patients with non-cardiac chest pain were excluded from the study. Cases with congenital and rheumatic heart disease, cardiomyopathies, unstable angina and acute MI were excluded. Patients with IHD with or without myocardial infarction (MI) were studied for left ventricular dysfunction (ejection fraction, left atrial size, E/A ratio), wall motion abnormalities and complications of IHD (Mitral regurgitation, Ventricular Septal Defect (VSD), LV aneurysm, LV clot). Clinical and echocardiographic evaluation was done in each case. Results: Out of 183 cases of chronic IHD, 123 patients were without previous MI and 60 had had previous MI. Ejection fraction (EF) was 45%±15 in the group without MI and 35±11% in cases with MI. Left Atrium (LA) size was 35±6 mm and 39±4 mm in the two groups respectively. LV diastolic dysfunction was seen in 17% in the first and 24% in the second group respectively. Global hypokinesia was seen in 8% and 17% in the 2 groups respectively. Regional Wall Motion Abnormality (RWMA) was observed in 12% in patients without MI and in 58% cases with MI. Mitral regurgitation was seen in 10 and 20% in the 2 groups respectively LV clots, VSD, LV and aneurysm were seen in 8.4, 5, and 6.5% respectively, only in cases with previous MI. Conclusion: LV dysfunction, wall motion abnormalities and mitral regurgitation were more common in IHD cases with previous heart attack. Keywords: Ischemic heart disease, left ventricular dysfunction, Wall motion abnormalities, Mitral regurgitation